Mikla Katherine Lewis interviewed by Gregg Borschmann in The people's forest oral history project - Lewis, Mikla (Mikla Katherine), 1953-; Borschmann, Gregg (Gregg John), 1955- (1997)
Mikla Lewis, a naturalist, speaks of her years of experience in working to rescue the native flora and fauna from sprawling urban development which was eliminating remnant bushland; of how in 1984 she and a small group of people set up the NSW Wildlife Information & Rescue Service (WIRES) starting in Sydney, then spreading throughout the State; how in 1995 at Blackheath, NSW, Lewis launched a network of volunteers for plant rescue called the Blue Mountains Wild Plant Rescue Service.
Recorded on Mar. 10 and July 1 1997 in Blackheath NSW.
Digital master available
Timed summary and corrected transcript available (typescript, 60 leaves).
Keywords: Lewis, Mikla -- 1953- -- Interviews; New South Wales Wildlife Information and Rescue Service; Blue Mountains Wild Plant Rescue Service (N.S.W.); Plant collectors -- New South Wales; Plant conservation -- New South Wales; Naturalists -- New South Wales -- Interviews; Seed collectors; Naturalists